Removal of Cu(II) Ions by Leucaena Leucocephala (Subabul) Seed Pods from Aqueous Solutions - A. K. Patil; V. S. Shrivastava (E-Journal of Chemistry)
In this method, Leucaena leucocephala seed pods (LLSP) have been used for removal of Cu(II) ions from aqueous solution. Batch adsorption experiments were conducted to study the effect of process parameters like pH, contact time initial Cu(II) ions concentration and adsorbent dose. The maximum adsorption of Cu(II) ions on Leucaena leucocephala seed pods was 94.17% at pH 5. The amount of metal adsorbed per unit weight of adsorbent increases with time and reach equilibrium after 30 minutes of shaking time for the different initial metal concentrations. The Freundlich and Langmuir isotherm equations were applied for the equilibrium adsorption data and the various isotherm parameters were evaluated. The obtained plots were linear as evident from R2 values close to unity. The data agreed very well with the pseudo second-order kinetic model.